Edukasi dan Pemberdayaan Masyarakat dalam Meningkatkan Partisipasi Kegiatan Kebersihan Lingkungan - Nelud Darajaatul Aliyah; Siti Rochani; Rahayu Mardikaningsih; Yeni Vitrianingsih; Ernawati Ernawati (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Community participation in environmental cleanliness activities is an important factor in realizing a healthy, comfortable, and sustainable environment. However, the level of participation is greatly influenced by the quality of environmental education and community empowerment programs carried out by various parties, including the government, educational institutions, and social organizations. This service activity aims to analyze how environmental education and community empowerment can increase citizens' awareness, willingness, and direct involvement in environmental cleanliness activities. This activity uses a descriptive approach combined with the Participatory Action Research (PAR) method, which involves the community directly in the process of identifying problems, planning, action, and reflection related to cleaning activities, as well as mapping the community's local assets and potential, such as the ability of residents, youth groups, village facilities, and the support of educational institutions, as the main driving force for cleaning activities. Education is provided through counseling, coaching, group discussions, and hands-on practice, while empowerment is carried out by providing space for the community to be involved in decision-making and implementation. The results of the analysis show that sustainable education is able to increase public understanding of the importance of environmental cleanliness, while empowerment through Participatory Action Research (PAR) fosters a sense of belonging, independence, and responsibility for the community. Both have been proven to have a significant influence on increasing community participation in environmental cleanliness activities.